Effect of early water contact on solubility of glass ionomer luting cements - (:unkn) unknown (MOSBY-YEAR BOOK INC, 1998)
Statement of problem. Glass ionomer cements are susceptible to attack by moisture during the initial setting period that can result in an increased solubility. Purpose. This study was to evaluate the solubility of glass ionomer luting cements immersed in distilled water at early stages after mixing. Material and methods. Four commercial glass ionomer cements were used (Ketac-Cem, Fuji Ionomer I; AquaCem; AquaMeron). For each material, 5 resin cement holders were made with 2 circular cavities (diameter = 5 mm; depth = 2 mm). One minute after start of mixing, the specimens were placed in a humidifier at 37 degrees C and 100% relative humidity. After 2, 5, and 8 minutes storage time, they were immersed in 50 mL of distilled water in a glass weighing bottle where they were stored for 3 hours at 37 degrees C. Next, the specimens were removed and the water was evaporated from the weighing bottle at 130 degrees C for 2 hours. The difference between the final and initial weights of the bottle was taken as amount of solubility. Data were analyzed by analysis of variance and Duncan's test. Results. Solubility was greatest at 3 minutes immersion time and least at 9 minutes. The lowest cement loss was for AquaCem at 9 minutes immersion time (1.68 mg/cm(2)). The greatest loss was for Fuji Ionomer I after 3 minutes immersion time (14.98 mg/cm(2)). Solubility of cements decreased by 39% for Ketac-Cem, 61% for Fuji Ionomer I, 38% for AquaCem, and 37% for AquaMeron when the specimens were immersed in water 6 minutes after mixing. Comparison of all 4 cements revealed a relatively large difference between loss of substance from AquaCem and AquaMeron, and the 2 other conventional glass ionomer cements, Ketac-Cem and Fuji Ionomer I. Conclusions. Increasing the time from start of mixing until immersion in water from 3 to 9 minutes resulted in a marked decrease in loss of substance from the surface of all 4 cements. Water-hardening glass ionomer cements (AquaCem and AquaMeron) were less sensitive to early water contamination.
Keywords: CLINICAL-EVALUATION; EROSION